An Analysis of Grammatical and Mechanical Errors in LIUNIC ON THINGS Products’ Captions - Moreno, Muhamad Julio; Meilinda, Lina; Bakhti, Krisna Yudha (Jurnal Bahasa Inggris Terapan, 2023)
Captions are one of the most important elements in social media because they can provide context, add narrative, or engage the audience with the posted content. However, captions that are written sometimes do not comply with the language rules used. This study aims to identify the kinds of grammatical and mechanical errors found in the captions of LIUNIC ON THINGS. The study applied theories from Dulay, Burt, and Krashen's Surface Strategy Taxonomy (1982), Warriner and Griffith (1973), and Mitchell (2008). This study applied a document analysis method; the process of reviewing and evaluating documents both printed and electronic in a methodical manner. This method is useful for identifying, categorizing, analyzing, and interpreting physical data to gain understanding and come to a conclusion. From the data collection, it was found that there were 66 grammatical errors and 61 mechanical errors in 50 captions released in 2022. The results revealed that the grammatical errors found in its Instagram caption are 63.6% of misformation, 25.8% of omission, 6.1% of misordering, and 4.5% of addition. The mechanical errors, on the other hand, are 50.8% of punctuation errors, 44.3% of capitalization errors, and 4.9% of spelling errors. It can be seen that misformation is the most common grammatical error, and punctuation is the most common mechanical error. The result of this study is expected to be used as one of the evaluation resources for social media caption makers to prevent the occurrence of grammatical and mechanical errors.